The Impact of Defense Policy on Quality of Life, Poverty, and Inequality - Aris Sarjito; Nora Lelyana (Journal of Government and Politics (JGOP), 2024)
Defense policies, traditionally focused on national security, have extensive implications for a country's socio-economic structure, influencing quality of life, poverty, and inequality. This research aims to explore the complex relationship between defense spending and these socio-economic outcomes across different contexts. Using a qualitative approach, the study utilizes secondary data from academic journals, government reports, and policy documents to analyze how defense policies impact various socio-economic groups. The findings reveal that in wealthier nations, defense spending can stimulate economic growth but often exacerbates social inequality due to the unequal distribution of benefits. In contrast, in less wealthy nations, high military expenditure typically comes at the expense of essential public services, leading to increased poverty and poorer health outcomes. The study also highlights the critical role of governance in mediating these effects, with strong institutions ensuring more equitable outcomes. In conclusion, defense policies have a profound impact on socio-economic conditions, and a context-specific approach is essential to ensure that national security investments do not undermine social welfare.Keywords: defense policy, inequality, poverty, quality of life, socio-economic impact